Green synthesis of silver nanoparticles from purple acid phosphatase apoenzyme isolated from a new source limonia acidissima - Pawar, Omkar; Deshpande, Neelima; Dagade, Sharda; Waghmode, Shobha; Joshi, Preeti Nigam (Journal of Experimental Nanoscience, 2016)
Green synthesis of nanoparticles is regarded as a safe and non-toxic process whereas conventional synthesis using chemical methods produces toxic substance. This study provides a novel insight for enzymatic synthesis method of silver nanoparticles using purple acid phosphatase, isolated from Limonia acidissima (wood apple) as a new source and used in the synthesis of silver nanoparticles. Stable silver nanoparticles were produced by sonochemical method using apoenzyme as a stabilising and capping agent and were characterised by various physicochemical techniques like UV-Visible spectroscopy, Fourier-transform infrared, X-ray diffraction and transmission electron microscopy. X-ray study shows that nanoparticles are composed of silver and silver oxide. The synthesised nanoparticles exhibited excellent antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus.
Keywords: green synthesis; Limonia acidissima; purple acid phosphatase; silver nanoparticles